Pharmacologic Effects of 4-Chlorophenol in Rats: Comparison to Clofibrate - Srichan Phornchirasilp (2018)
4-Chlorophenol (4-CP) is an identified trace contaminant in commercial clofibrate preparations and the pharmacologic effects of 4-CP have not yet been widely established. We have examined the dose-dependent effects of oral 4-CP and clofibrate administration on selected hepatic parameters and on serum glucose, cholesterol, and triglyceride concentrations in male rats. 4-CP treatment (0.00125-0.08 mmol/kg, twice a day) of rats for 2 weeks increased hepatic microsomal protein (20-30%) and cytochrome P-450 (20-190%) contents without changing liver/body weight ratios. Both 4-CP (0.0025 mmol/kg body wt, twice a day) and CPIB (0.4 mmol/kg body wt, twice a day) treatment to rats for 2 weeks caused significant elevations in microsomal cytochrome P-450 content and in the maximal activities of ethylmorphine, aminopyrine, and benz-phetamine N-demethylase, but not in the activity of zoxazolamine 6-hydroxylase. With the same dose of 4-CP, time-dependent increases in hepatic microsomal protein, cytochrome P-450, and the activity of benzphetamine N-demethylase were observed for a 4-week period, and the induction of hepatic microsomal benzphetamine N-demethylase activity by 4-CP was associated with an increased enzyme synthesis. 4-CP treatment produced a marked morphologic change in liver cell ultrastructure, including a proliferation of mitochondria and endoplasmic reticulum at lower 4-CP doses. A clustering of intracellular organelles (mitochondria and endoplasmic reticulum) and a foamy cytoplasm were seen at doses greater than 0.01 mmol/kg, twice a day for 2 weeks, and at 0.0025 mmol/kg, twice a day for > 4 weeks. The effects of 4-CP and clofibrate on fasting blood glucose and fasting serum lipid levels were also monitored throughout an 8-week period. Both 4-CP (0.005 mmol/kg body wt, twice a day) and clofibrate (0.2 mmol/kg body wt, twice a day) produced significant elevations in fasting serum glucose levels, but this dosage of 4-CP did not alter serum lipid and lipoprotein parameters, whereas clofibrate significantly reduced serum total cholesterol and high density lipoprotein cholesterol levels. These results lead us to conclude that 4-CP does not contribute to the antilipidemic effects of clofibrate. © 1989, SAGE Publications. All rights reserved.